2012
DOI: 10.1073/pnas.1116523109
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of medial prefrontal cortex neurons during alcohol withdrawal predicts cognitive impairment and excessive alcohol drinking

Abstract: Chronic intermittent access to alcohol leads to the escalation of alcohol intake, similar to binge drinking in humans. Converging lines of evidence suggest that impairment of medial prefrontal cortex (mPFC) cognitive function and overactivation of the central nucleus of the amygdala (CeA) are key factors that lead to excessive drinking in dependence. However, the role of the mPFC and CeA in the escalation of alcohol intake in rats with a history of binge drinking without dependence is currently unknown. To add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
178
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(202 citation statements)
references
References 33 publications
17
178
1
Order By: Relevance
“…The lack of differences in MCSF performance between waterand alcohol-drinking rats following a period of voluntary alcohol intake is in line with previous studies in which other behavioral tests were used [37,38] and also following after a period of abstinence [38]. However, previous studies have revealed contrasting results with both increased activity [17] and decreased activity [18] on the open arms of the elevated plus maze following voluntary alcohol intake relative to water-drinking controls.…”
Section: Behavior In Water-and Alcohol-drinking Ratssupporting
confidence: 88%
“…The lack of differences in MCSF performance between waterand alcohol-drinking rats following a period of voluntary alcohol intake is in line with previous studies in which other behavioral tests were used [37,38] and also following after a period of abstinence [38]. However, previous studies have revealed contrasting results with both increased activity [17] and decreased activity [18] on the open arms of the elevated plus maze following voluntary alcohol intake relative to water-drinking controls.…”
Section: Behavior In Water-and Alcohol-drinking Ratssupporting
confidence: 88%
“…These data support the further use and development of noradrenergic agents for the treatment of PTSD, and are in strong accordance with the demonstrated efficacy of prazosin in both preclinical models (Olson et al , 2011) and PTSD patient populations (Raskind et al , 2003) (Krystal and Neumeister, 2009). Finally, excessive alcohol exposure and dependence itself may contribute to dysregulated signaling in the PFC (George et al , 2012; Kim et al , 2014), leading to the development or exacerbation of PTSD-associated symptoms in rodents (Holmes et al , 2012), consistent with the human literature (Tipps et al , 2014; Perrin et al , 2014). …”
Section: Recent Neurobiological Insights Gained From Animal Models Ofsupporting
confidence: 76%
“…The rodent mPFC also has functional similarity to the dorsolateral prefrontal cortex in primates (Kolb, 1984; Birrell and Brown, 2000; Barense et al, 2002; Seamans et al, 2008; Kesner and Churchwell, 2011). Chronic alcohol abuse and alcohol dependence can result in impaired performance on cognitive tasks associated with integrity of the mPFC (George et al, 2012; Kroener et al, 2012), suggesting that this region undergoes neuroadaptive change with prolonged exposure to moderate to high alcohol levels. We posit that repeatedly engaging in binge alcohol exposure stimulates HPA axis activity and leads to enduring GR signaling within the mPFC that produce changes in functions dependent on this region.…”
Section: Glucocorticoids May Target the Medial Prefrontal Cortex (Mpfmentioning
confidence: 99%